Integrating Technology into Science Learning in Junior High School: Perspective of Teachers - Anggi Datiatur Rahmat; Heru Kuswanto; Insih Wilujeng (Jurnal Penelitian Pendidikan IPA, 2023)
Technology has a positive role in improving students' learning abilities. The teacher has the leading role in implementing technology in the classroom. This study aims to introduce technology that can be integrated into science learning and report the perspective of science teachers with different educational backgrounds in integrating technology into the learning process. The study uses a qualitative method by using interviews to collect data. The participants were selected randomly from the Association of Science Education Teachers in West Bandung, Indonesia. Six teachers chose to be interviewed based on different teaching experiences and educational backgrounds. The study found that science teachers with different educational backgrounds have different perspectives on the difficulty of teaching science concepts. But they have the same solution to this problem: integrating technology into the learning process. All participants in this study have experience integrating technology in learning but are the first experience in using AR technology. Various technologies are considered appropriate for integration into science learning, but AR technology that can visualize abstract concepts has the potential to be used more in education